2010
DOI: 10.1111/j.1476-5381.2010.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

The Electro‐Mechanical window: a risk marker for Torsade de Pointes in a canine model of drug induced arrhythmias

Abstract: In cardiovascular pharmacology, electrical and mechanical events can be distinguished, and the phrase 'electro-mechanical window' (EMw) describes the temporal difference between these events. We studied whether changes in EMw have potential predictive value for the occurrence of arrhythmias in fentanyl/etomidate-anaesthetized beagle (FEAB) dogs. EXPERIMENTAL APPROACHThe EMw was calculated as differences between the QT interval and QLVPend in FEAB dogs during atrial pacing, treatment with isoprenaline or atropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
91
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 41 publications
12
91
0
1
Order By: Relevance
“…More recently, these clinical findings were substantiated by animal studies, which demonstrate that the negative EM window markedly increases susceptibility to life-threatening ventricular tachyarrhythmia, such as torsade de pointes [6], [8][9]. In a canine model of long QT syndrome, a negative EM window was found to be a prerequisite for VT initiation [6]. In anesthetized guinea-pigs, administration of drugs with known high proarrhythmic potential (i.e., quinidine, haloperidol, and domperidone) was found to induce a negative EM window, whereas safe antiarrhythmics such as amiodarone, verapamil and diltiazem produced no effect [8][9].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…More recently, these clinical findings were substantiated by animal studies, which demonstrate that the negative EM window markedly increases susceptibility to life-threatening ventricular tachyarrhythmia, such as torsade de pointes [6], [8][9]. In a canine model of long QT syndrome, a negative EM window was found to be a prerequisite for VT initiation [6]. In anesthetized guinea-pigs, administration of drugs with known high proarrhythmic potential (i.e., quinidine, haloperidol, and domperidone) was found to induce a negative EM window, whereas safe antiarrhythmics such as amiodarone, verapamil and diltiazem produced no effect [8][9].…”
Section: Discussionmentioning
confidence: 89%
“…Importantly, in patients with healed myocardial infarction, the long-term survival rate was found to be 2.6-fold lower in a patient subgroup with a negative EM window, thereby indicating that this parameter may be used to predict the mortality risk in coronary artery disease [3]. More recently, these clinical findings were substantiated by animal studies, which demonstrate that the negative EM window markedly increases susceptibility to life-threatening ventricular tachyarrhythmia, such as torsade de pointes [6], [8][9]. In a canine model of long QT syndrome, a negative EM window was found to be a prerequisite for VT initiation [6].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1 In follow-up studies, conscious dogs (n¼6; telemetered) showed comparable baseline values to anaesthetised dogs (n¼20): QT¼250 vs 252 ms, QLVPend¼347 vs 339 ms and EMw¼+96 vs +87 ms, respectively. To compare the EMw in conscious and anaesthetised dogs after IKs blockade.…”
mentioning
confidence: 89%
“…Drug-induced cardiotoxicity is a major concern to the pharmacological industry and it is one of the main reasons for non-approval, re-labelling, warnings and withdrawal of pharmaceutical compounds from the market. 1 Doxorubicin is an anthracycline antibiotic used in cancer therapy. Although issues relating to Doxorubicin and cardiac safety have been well established in normal conditions, the effects of this drug on the myocardium during ischaemia-reperfusion have not been investigated in detail to date.…”
mentioning
confidence: 99%